Building low-cost intelligent building components with Controller Area Network (CAN) bus - Hooi T.C.; Singh M.; Siah Y.K.; Bin Ahmad A.R. (2023)
Intelligent Buildings is a concept that was derived from Theory of AI and has recently being realized by the increasing coverage and reliability of telecommunication equipment and Information Technology. Many of the intelligent building systems however, are derived from either building automation technologies such as Profibus, ASHRAE's BACNET or home automation protocols like X10, BatiBus, EIB, HomeBus, CEBus and perhaps the more remarkable Echelon's LonWorks. Most of the networks mentioned above did not offer enough bandwidth for voluminous data except for BACNet, and Profibus. Robustness under harsh condition has yet to be addressed by the above technologies. This paper will look into the construction of Controller Area Network (CAN) bus network (a cost-effective communication bus for in-car electronics with up to 1Mbit/sec and is resilient to extreme heat and harsh environments) to support intelligent building requirements as well as solving the problem of low bandwidth and robustness.